Optimization of Cu2O Thickness to Enhance Photocatalytic Properties of Electrodeposited Cu2O/FTO Photoanode - Khasanah, Riza Ariyani Nur; Chien, Forest Shih-Sen; Prasetyowati, Rita; Yudianti, Rike (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Currently, n-type cuprous oxide (Cu2O) is a promising material as photocatalyst because of its energy gap of 2 eV that absorbs visible light up to a wavelength of 600 nm. As a photoelectrode, the thickness of Cu2O is crucial, where the improper thickness may worsen the photocatalytic properties. This work aimed to enhance the photocatalytic properties of Cu2O electrodeposited on fluorine-doped tin oxide (FTO), called Cu2O/FTO, by optimizing the Cu2O thickness. The thickness of Cu2O was controlled by adjusting the deposition time in the electrochemical deposition of Cu2O/FTO. By changing the deposition time from 5 to 45 min, the morphology of Cu2O changed from a leaf-like shape to an irregular facet shape with highly dense coverage, and the average thickness increased from 370 to 1100 nm. The increasing Cu2O thickness resulted in the increasing light absorption. The Cu2O/FTO demonstrated anodic photocurrent, which increased with the Cu2O thickness up to a threshold value of 1000 nm (35 min deposition time). At a thickness of 1000 nm, Cu2O/FTO achieved the highest photocurrent (150 and 58 µA under irradiation of 365 and 470 nm, respectively) due to the highly dense morphology and high absorption. In addition, with a thickness of 1000 nm, the charge diffusion was still good. Further, the increase of Cu2O film thickness higher than 1000 nm caused low photocatalytic properties even though the morphology was highly dense, and the absorption was the highest. This condition could be due to the relatively too-high resistance of Cu2O that caused poor charge diffusion. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).